Evoluzione della chirurgia sostitutiva del polso e mano - Dutto, E.; Ferrero, M.; Teodori, J.; Piccato, A.; Battiston, B. (Lo Scalpello - Journal, 2019)
EVOLUTION OF WRIST AND HAND PROSTHETIC SURGERY Prosthetic development in the treatment of arthritis is an important part of modern orthopaedics. As regards the wrist, prostheses have been introduced only recently, owing to the lower incidence of degenerative problems and satisfactory surgical alternatives. Biomechanical studies and evolutions in engineering have led to the development of new models, which are less invasive compared to those used in the past. The goal of this development is treating arthritis localised between the single carpal bones and preserving the function in case of total radio-carpal arthroplasty. As regards the interphalangeal and metacarpophalangeal joints, they can be treated with prostheses instead of arthrodesis or biological arthroplasty, on the basis of the biomechanical function of every single joint and of the patient’s needs; however, recovering mobility and functionality is more complicated than in case of wrist implants.